Photoluminescence investigation of strictly ordered Ge dots grown on pit-patterned Si substrates. (13th May 2015) - Brehm, Moritz; Grydlik, Martyna; Tayagaki, Takeshi; Langer, Gregor; Schäffler, Friedrich; Schmidt, Oliver G
Abstract: We investigate the optical properties of ordered Ge quantum dots (QDs) by means of micro-photoluminescence spectroscopy (PL). These were grown on pit-patterned Si(001) substrates with a wide range of pit-periods and thus inter QD-distances (425–3400 nm). By exploiting almost arbitrary inter-QD distances achievable in this way we are able to choose the number of QDs that contribute to the PL emission in a range between 70 and less than three QDs. This well-defined system allows us to clarify, by PL-investigation, several points which are important for the understanding of the formation and optical properties of ordered QDs. We directly trace and quantify the amount of Ge transferred from the surrounding wetting layer (WL) to the QDs in the pits. Moreover, by exploiting different pit-shapes, we reveal the role of strain-induced activation energy barriers that have to be overcome for charge carriers generated outside the dots. These need to diffuse between the energy minimum of the WL in and between the pits, and the one in the QDs. In addition, we demonstrate that the WL in the pits is already severely intermixed with Si before upright QDs nucleate, which further enhances intermixing of ordered QDs as compared to QDs grown on planar substrates. Furthermore, we quantitatively determine the amount of Ge transferred by surface diffusion through the border region between planar and patterned substrate. This is important for the growth of ordered islands on patterned fields of finite size. We highlight that the Ge WL-facets in the pits act as PL emission centres, similar to upright QDs.